LEGAL BACKGROUND FOR THE ACCOUNTING CONCEPT OF REALIZATION. - Windal, Floyd W. (The Accounting Review, 1963)
The legal concept of realization has developed gradually over a period of about eighty years, and even today is not a completely static idea. It does, however, occupy a place of importance in law as an integral part of the legal concept of income. No income is deemed to arise until "realization" has taken place. The development of this concept may be traced back to the days when income was regarded as the difference in the value of net worth between two points of time. Any increase or decrease in the value of assets between these two points of time thus affected the net income figure. The break away from this point of view came in 1861, at the start of the Civil War, when the federal government passed an income tax law which defined income as the excess of cash receipts over cash payments. Thus a new theory of income computation was established, and with it a theory of realization. Income was conceived of as a "net" figure, which required the evidence of cash receipts. This point of view prevailed throughout the administration of the Civil War tax laws up to 1871. From 1872 to 1909 there was no federal income tax law in effect. Finally in 1909 a federal excise tax based on income was passed. The same concept of income that had prevailed from 1861 to 1871 was embodied in that law. The excess of cash receipts over cash payments was the measure of income. In ensuing years the strict cash requirement was modified. The concept of "cash or its equivalent" came into being, and was followed by the concept of "the completed transaction." Thus, from the requirement that cash alone must be the evidence of realization, it became generally accepted that a valid account receivable was sufficient. The sale became the test of realization for the majority of situations. About 1913, the courts began to express a new concept of income. They began to conceive of income as the "gain derived from capital, from labor, or from both combined."